2019
DOI: 10.1007/s42452-019-1472-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the reservoir operation planning with the climate change adaptation

Abstract: The management planning of Pedu-Muda reservoir, Kedah, was investigated in the context of the climate change evolution. The aim of this study was to evaluate the impact of the climate change to the reservoir operating management system and its sustainability. The study was divided into two sections; Analysis 1 refers to the reservoir optimization adapted with the climate assessment. The statistical downscaling model reacted as the climate model to generate the long-term pattern of the local climates affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the use of optimized rule curves partly mitigated the climate change effects in terms of the water supply failure, irrigation water deficit, and drought damage. Concurrently, some studies evaluated the effect of changes in reservoir management criteria on climate change and found that the implemented adaptation strategies can significantly reduce the adverse effects of climate changes on the future water supply (Ashofteh, Rajaee, Golfam, & Chu, 2019; Tukimat & Harun, 2019). Among all, very few studies come up with adaptation strategies by the reservoirs that could solve the future drought and water supply problems completely, which further calls for the combined adaptation options.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of optimized rule curves partly mitigated the climate change effects in terms of the water supply failure, irrigation water deficit, and drought damage. Concurrently, some studies evaluated the effect of changes in reservoir management criteria on climate change and found that the implemented adaptation strategies can significantly reduce the adverse effects of climate changes on the future water supply (Ashofteh, Rajaee, Golfam, & Chu, 2019; Tukimat & Harun, 2019). Among all, very few studies come up with adaptation strategies by the reservoirs that could solve the future drought and water supply problems completely, which further calls for the combined adaptation options.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several models have been developed to provide adaptive operational rules to consider such induced climate change operational risk. In this respect, the integration of climate, hydrology, and optimization models are used to provide adaptive dam operation rules for various climate change scenarios [119][120][121][122][123][124][125].…”
Section: Topic 2: Climate Changementioning
confidence: 99%
“…This is not possible in many cases due to the large number of decision variables and the increase in computational costs as well as discontinuity in the goal space. In order to solve this problem in the last two decades, meta-heuristic methods such as Evolutionary Algorithm (EA), methods based on Swarm Intelligence (SI) and algorithms based on simulating physical and chemical laws have been widely used in solving multi-objective models for reservoir water resource planning (Fang & Popole, 2020;KhazaiPoul et al, 2019;Mansouri et al, 2022;SeethaRam, 2021;Sharifi et al, 2021;Tang et al, 2020;Tukimat & Harun, 2019;Yang et al, 2020). In this regard, Yaghoubzadeh-Bavandpour et al compared the performance of SI and EA algorithms for the optimal management and planning of water resources in the operation of reservoirs (Yaghoubzadeh-Bavandpour et al, 2022).…”
Section: Introductionmentioning
confidence: 99%